Location-based Games as Interfaces for Collecting User Data - Rauti Sampsa; Laato Samuli (Germany, 2022)
Location-based games (LBGs) are becoming increasingly popular. These games use player's physical location as a game mechanic, and many of the games are played in real time. This study investigates the affordances that three popular LBGs, Ingress, Pokémon GO and The Walking Dead: Our World, provide for users to collect location data from other players. To this end, the game mechanics of the games and the end user privacy policies are analyzed and compared together. The results reveal several privacy concerns which are not currently adequately addressed in the privacy policies of the games. As LBGs are becoming increasingly complex, the risk of unwanted player data collection opportunities rises, combating which is predicted to be a major design challenge for LBG developers in the future.
Trends and Innovations in Information Systems and Technologies: Volume 2